Manfaat Alat Pembayaran Menggunakan Kartu (APMK) Pada Masyarakat Kota Tegal - Kartikasari, Maulida Dwi (PERMANA, 2019)
This research aims to find out the benefits of using the Card Payment Inatrument in Tegal. This research was conducted in the Tegal by taking 100 respondents to visitors shopping center in Tegal. The respondent despite into two groups, 50 male respondents and 50 female respondents this research use qualitative method. Respondents were randomly selected and the data were collected based on in depth interview results. The results of this research show that the Card Payment Method has a huge benefit for its users. Some societies state. able to bring cost-effective behavior because it can control spending. Of money. However, there are also people who give the perception that APMK is a secure payment instrument because mostly card has a Personal Indentification Number in it. Some of respondents sid that Card Payment Method are able to avoid the crime of counterfeit money